Synthesis and biological evaluation of new pyrazoline derivatives of diarylpentadienone - Auwal, Adam Faruk (2020)
Diarylpentadienone and pyrazoline analogues were reported to have excellent pharmacological activities including antioxidant, anti-inflammation, and anti-cancer with extremely low toxicity. A number of synthetic phenolic antioxidants such as butylated hydroxytoluene (BHT) and butylated hydroxy anisole (BHA) have been widely used in the food industry, cosmetics, and the therapeutic industry, however, have been reported to be dangerous to humans due to their high volatility, instability at elevated temperature and its carcinogenic nature. Thus, led to the growing needs for new antioxidant agents for an alternative safe treatment. A series of the diarylpentadienones (1-10) are firstly prepared using Claisen-Schmidt condensation reaction, before further reacted with hydrazine hydrate under reflux to obtain the new series of pyrazoline analogues (11-19). The structures of the synthesized compounds were confirmed via 1H-, 13C- and 2-dimensional Nuclear Magnetic resonance (NMR) as well as Fourier Transform Spectroscopy (FTIR) and Direct injection-Mass Spectroscopy (DIMS) analyses. Following that, the antioxidant capacity of the synthesized molecules is determine using 2,2-diphenyl-1-picrylhydrazine (DPPH) radical and nitric oxide (NO) scavenging assays while quercetin is use as the positive control. The results disclose that compounds 1-(2,4-dimethoxyphenyl)-5-(4-methoxyphenyl)penta-2,4-dien-1-one (4) and 1-(3-(3-fluorophenyl)-5-(4-methoxystyryl)-4,5-dihydro-1H-pyrazol-1-yl)ethenone (16) show good activity in the DPPH free radical scavenging activity with IC50 values of 1.32±0.015 μg/mL and 1.55±0.029 μg/mL when compared to standard quercetin (IC50 : 1.61±0.010 μg/mL); and significant NO scavenging activity with IC50 values of 6.13±0.089 μg/mL and 5.97±0.081 μg/mL in comparison to the standard quercetin and gallic acid with IC50 values of 1.91±0.006 μg/mL and 0.88±0.010 μg/mL, respectively. Meanwhile, other compounds demonstrate moderate to lower DPPH and NO scavenging activity. Simple SAR study reveal that remarkable antioxidant properties depends on the presence of 2,4-dimethoxy phenyl ring on diarylpentadienone and 3-flouro phenyl ring on the pyrazoline derivatives. It is also proposed to prevent the use of high electron-donating group on pyrazoline if aimed to be having a potential antioxidant. Additionally, the compounds are also tested against selected acne-causing bacteria [Propionibacterium acnes (P. acne), Staphylococcus epidermidis (S. epidermidis) and Staphylococcus aureus (S. aureus)] and Candida albicans (C. albicans), through disc diffusion assay (DDA). However, it is noticeable that all molecules are ineffective towards the antibacterial and anti-candida assays. Therefore, it is conceivably concluded that diarylpentadienone and pyrazoline derivatives are potent families as antioxidant agents.